Tooth loss is associated with prevalent diabetes and incident diabetes in a longitudinal study of adults in Ireland. - Mc Garrigle, Christine (My University, 2024)
Aim: The aim of this study was to explore the relationship between periodontal status, tooth loss and diabetes among community-dwelling adults aged 50 years and over in Ireland. Methods: From respondents who attended a health assessment in Wave 3 of the Irish Longitudinal Study on Ageing (TILDA), an opportunistic sample was selected for an oral health examination. The oral health examination criteria were used in previ- ous Irish surveys and WHO recommendations. For diabetes, the self-reported and objectively measured data on diabetes for the same cohort from Wave 3 to Wave 5 of TILDA was used. Multinomial regression analysis was used to evaluate the relation- ship between diabetes and tooth loss and tooth loss and incident diabetes, controlling for other covariates. Results: Out of the 3111 people who were offered an oral health assessment 2539 were examined. For the purposes of analysis, the adults below 50 years of age (n = 31) and those with an incomplete oral health assessment (n = 4) were omitted from the sample. The final sample consisted of 2504 people, giving a response rate of 80.5%. Among the study sample, 9.9% (n = 249) were edentate; 35.7% (n = 895) had 1–19 teeth and 54.4% (n = 1360) had ≥20 teeth. From the sample of 2504 adults, 2358 had HbA1c results and 8.4% (n = 198) of these had diabetes according to the TILDA criteria. Multinomial regression analysis showed that diabetes was associated with tooth loss. Diabetes at Wave 3 was associated with a higher rate of being edentate (PR 2.12, 95% CI 1.27–3.52) relative to having ≥20 teeth while controlling for the effect of age, gender, education level, area of residence, body mass index (BMI) and smoking. Furthermore, having 1–19 teeth at Wave 3 was associated with incident diabetes over a 4-year follow-up (OR 1.94, 1.00–3.75). There was no evidence of an association between diabetes and periodontal status as measured in this sample. Conclusion: The results suggested that diabetes was associated with tooth loss and that this relationship may be bi-directional among community-dwelling adults aged 50 years and over in Ireland, but they do not support a relationship between diabetes and periodontal status in this sample.
PUBLISHED
Keywords: ageing, diabetes mellitus, glycated haemoglobin, periodontal disease, prediabetes, tooth loss